Improving nursing students' perspective taking, perceptions of humanness, and attitudes toward older adults. Issue 4 (2nd October 2021) - Miron, Anca M.; Schmidt, Bonnie J.; Schlueter, Amy; Patterson, Megan; O'Connell, Sarah
ABSTRACT: Whereas prior work has examined the role of nursing courses in improving empathic skills and reducing dehumanization of older adults, little research has explored how perspective taking and perceptions of humanness of older adults acquired through nursing curricula predict attitudes toward this age group. Nursing students ( N = 43) completed surveys at the beginning (Time 1) and end of gerontological coursework (Time 2). Perspective taking and perceived human nature and human uniqueness of older adults increased from Time 1 to Time 2. Perceived human nature of older adults was associated with more positive attitudes at the end of the semester, compared to the beginning. Improved perceptions of the human nature of older adults also predicted lower ageism at the end of the semester. Strategies for improving perspective taking and perceptions of humanness of older adults in nursing courses are discussed.